2005
DOI: 10.1172/jci24408
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen, oxidative stress, hypoxia, and heart failure

Abstract: A constant supply of oxygen is indispensable for cardiac viability and function. However, the role of oxygen and oxygen-associated processes in the heart is complex, and they and can be either beneficial or contribute to cardiac dysfunction and death. As oxygen is a major determinant of cardiac gene expression, and a critical participant in the formation of ROS and numerous other cellular processes, consideration of its role in the heart is essential in understanding the pathogenesis of cardiac dysfunction.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
377
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 612 publications
(405 citation statements)
references
References 124 publications
14
377
0
14
Order By: Relevance
“…Reactive oxygen species affect almost all of the major features of cardiac maladaptive remodeling, including the hypertrophic responses, vascular dysfunction and extracellular matrix remodeling [7, 40]. In our study, we found that TAC induced an increase in total ROS levels in the hearts, whereas this effect was substantially suppressed in mice with sesamin treatment.…”
Section: Discussionsupporting
confidence: 47%
“…Reactive oxygen species affect almost all of the major features of cardiac maladaptive remodeling, including the hypertrophic responses, vascular dysfunction and extracellular matrix remodeling [7, 40]. In our study, we found that TAC induced an increase in total ROS levels in the hearts, whereas this effect was substantially suppressed in mice with sesamin treatment.…”
Section: Discussionsupporting
confidence: 47%
“…At the molecular level, an increased generation of ROS will induce mitochondrial permeability transition pore (mPTP) opening, a loss of mitochondrial membrane potential, mitochondrial swelling and, ultimately, mitochondrial dysfunction [3,4]. A constant supply of O 2 is essential to sustaining cardiac function and viability [5]. In a high-altitude environment, the O 2 supply fails to match myocardial demand and cardiac contractile dysfunction occurs; prolongation of this imbalance may lead to apoptosis, necrosis and the release of proinflammatory cytokines such as TNF-α and IL-6 [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Iron has important roles in oxygen metabolism and energy capacity,18 and RLS is often associated with conditions involving hypoxia 19, 20, 21. Notably, baseline TSAT levels correlated significantly with improvement in IRLS scores at week 4 and EOS.…”
Section: Discussionmentioning
confidence: 99%